Registers for networked medical research in Germany - Stausberg, J.; Altmann, U.; Antony, G.; Drepper, J.; Sax, U.; Schütt, A. (Applied Clinical Informatics, 2010)
Background: Several disease specific registers are operated by members of the ‘TMF – Technology, Methods, and Infrastructure for Networked Medical Research’, an umbrella organization of research networks in Germany.Objective: To describe the coverage and the current state as well as financial and organizational issues of registers operated by member networks of the TMF, to identify their requirements and needs, and to recommend best practice models.Methods: A survey with a self-completion questionnaire including all 55 TMF member networks was carried out in winter 2007/2008. Interviews focusing on technological issues were conducted and analyzed in summer 2009 with a convenience sample of 10 registers.Results: From 55 TMF member networks, 11 provided information about 14 registers. Six registers address diseases of the circulatory system with more than 150,000 registered patients. The interviews revealed a typical setting of “research registers”. Research registers are an important mean to generate hypotheses for clinical research, to identify eligible patients, and to share data with clinical trials. Concerning technical solutions, we found a remarkable heterogeneity. The analysis of the most efficient registers revealed a structure with five levels as best practice model of register management: executive, operations, IT-management, software, hardware.Conclusion: In the last ten years, the TMF member networks established disease specific registers in Germany mainly to support clinical research. The heterogeneity of organizational and technical solutions as well as deficits in register planning motivated the development of respective recommendations. The TMF will continue to assist the registers in quality improvement.
Keywords: Competence Networks; documentation; register protocol; registers